Transient bold activity locked to perceptual reversals of auditory streaming in human auditory cortex and inferior colliculus - Schadwinkel, Stefan; Gutschalk, Alexander (Journal of neurophysiology, 2011)
Our auditory system separates and tracks temporally interleaved sound sources by organizing them into distinct auditory streams. This streaming phenomenon is partly determined by physical stimulus properties but additionally depends on the internal state of the listener. As a consequence, streaming perception is often bistable and reversals between one- and two-stream percepts may occur spontaneously or be induced by a change of the stimulus. Here, we used functional MRI to investigate perceptual reversals in streaming based on interaural time differences (ITD) that produce a lateralized stimulus perception. Listeners were continuously presented with two interleaved streams, which slowly moved apart and together again. This paradigm produced longer intervals between reversals than stationary bistable stimuli but preserved temporal independence between perceptual reversals and physical stimulus transitions. Results showed prominent transient activity synchronized with the perceptual reversals in and around the auditory cortex. Sustained activity in the auditory cortex was observed during intervals where the ΔITD could potentially produce streaming, similar to previous studies. A localizer-based analysis additionally revealed transient activity time locked to perceptual reversals in the inferior colliculus. These data suggest that neural activity associated with streaming reversals is not limited to the thalamo-cortical system but involves early binaural processing in the auditory midbrain, already.
Gesehen am 07.10.2022